IMPROVEMENT OF INVENTORY MANAGEMENT SYSTEM TO ACHIEVE COST EFFICIENCY AT PT. MEDICA UTAMA - Anjani, Andan
The increasing demand for imports of medical devices every year and the high demand for health workers, especially in the eye health sector, impact the growing demand for medical devices. Meanwhile, 90% of Indonesia's medical devices still depend on imports, thus making distributors the main players to meet domestic needs. Therefore, inventory management is an important thing that distributors should pay attention to. A suitable ordering system related to the amount and order time is required to minimize expend due to the overstock and losses due to stockout. This research aims to observe current inventory management applied by PT Medica Utama, as one of the medical equipment distributors specializing in eye health devices, and provide recommendations for an optimal inventory management system to achieve cost efficiency afterward. The method used in this research is quantitative, focusing on processing and analyzing numerical data obtained from the company to calculate safety stock and the number of orders. In addition, ABC classification is also used in data processing to group items based on their value. Items belonging to class A (having a value of 80% for the company) will be used in the data processing. The next step is to conduct forecasting simulations for demand forecasts. The results of the forecast will be used for calculating the safety stock and order quantity. The output from the results of data processing and analysis in this study shows 67 items included in class A, which will then be processed using Minitab software for forecasting. Based on comparing the four forecasting methods, the one with the lowest error value is Trend Analysis. If the company can apply the storage method according to the fixed-time period model calculation, there is a potential savings of US $ 717,133 or 63% of the total overstock.